2010
DOI: 10.1080/15017410903309102
|View full text |Cite
|
Sign up to set email alerts
|

Hard-of-hearing children's sense of identity and belonging

Abstract: This study explores the process of identity construction for hard-of-hearing (HH) children in Sweden. Twenty-nine children aged 9Á16 years who attended special classes for HH students were interviewed. During this longitudinal study, all classes were moved from an oral to a signing school environment. The findings support the position that a bilingual HH identity exists. HH children often construct their identity by widening their reference group to include not just HH but also those who are 'almost the same'.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 18 publications
2
13
0
Order By: Relevance
“…The children with hearing loss revealed experiences of becoming excluded of mutual activities, which corresponds to other researchers' findings, too (e.g., DeLuzio & Girolametto, 2011). Children with hearing loss in Brunnberg's (2010) study reported that they do not have enough friends.…”
Section: Social Peer Support and Practical Solutionssupporting
confidence: 86%
See 2 more Smart Citations
“…The children with hearing loss revealed experiences of becoming excluded of mutual activities, which corresponds to other researchers' findings, too (e.g., DeLuzio & Girolametto, 2011). Children with hearing loss in Brunnberg's (2010) study reported that they do not have enough friends.…”
Section: Social Peer Support and Practical Solutionssupporting
confidence: 86%
“…) Children with hearing loss need various hearing aids that can be stigmatizing. Brunnberg (2010) noted that a hearing aid and CI are symbols of handicap because using them makes hearing loss visible. However, hearing aids do not turn children with hearing loss normally hearing children.…”
Section: Challenges Of Communication Among Children With Hearing Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Personal characteristics that are considered important for social participation include an outgoing and friendly nature, a positive attitude, optimism and resilience (Oberle, Kimberly, and Kimberly 2010). In addition, students' opportunities to interact with peers with similar HL have consequences for their social participation rate (Brunnberg 2010). Interactions with hearing peers are considered more challenging and are characterized as vertical relationships, whereas interactions with children with similar disabilities are characterized as horizontal relationships.…”
Section: Introductionmentioning
confidence: 99%
“…This finding is in agreement with previous findings indicating that most important educational experiences for the development of DHH people’s identity are related to their interactions with, and support from, school peers. However, this affects specific identity profiles (Brunnberg, 2010; Hadjikakou & Nikolaraizi, 2007; Israelite et al, 2002; Kemmery & Compton, 2014; Sisia, 2012). The study also found that many participants were bullied, especially by their hearing peers.…”
Section: Discussionmentioning
confidence: 99%